Perspectivas docentes sobre o ensino da educação física na educação infantil - Lucca Junior, Julio Cesar de (Universidade Federal de São Carlos, 2020)
Since 2018, the municipal education network of São Carlos (state of São Paulo) started some works within the school units with the intention of implementing the Common National Base and to adhered to the collaboration regime for the elaboration of the São Paulo curriculum approved by the National Education Council. However, these documents do not explicitly address children's physical education. The objective of the present study was to analyze the perspectives of Physical Education teachers on the teaching of this curricular component in early childhood education in the municipal school system of São Carlos/SP. The qualitative research used, as instruments of information collection, questionnaire and semi-structured interview with Physical Education teachers who teach classes in the area of early childhood education in the public council in question. Questionnaires were sent to the 34 Municipal Early Childhood Education Centers that have a Physical Education teacher and 22 returned, covering 23 schools. Subsequently, five teachers participated in the semi-structured interview, deepening the theme of the study. The data were analyzed qualitatively, reaching the following categories: 1. Elements related to the teaching and learning process, in which we analyzed the contents, teaching strategies and evaluation processes used by teachers according to the students' age, and 2 Preparation of teachers for teaching, which present their vision in relation to their teaching, continued education, curriculum guidance, structural problems and positive aspects of their practices. Thus, we observed that the teaching of Physical Education in early childhood education in the city of São Carlos/SP is fragmented and uncertain. Although the teachers indicate the preparation for teaching, we perceive the lack of clarity in distinguishing and conceptualizing essential elements for this exercise. We highlight the relevance of studies that seek to map the teaching perspectives and awaken the need to create guiding documents and continuing education courses.
Teaching perspectives on the teaching of physical education in early childhood education
Keywords: Educação física escolar; Educação infantil; Orientação curricular; School physical education; Early childhood education; Curriculum guidance; CIENCIAS DA SAUDE::EDUCACAO FISICA